(untitled) (KULT_online, 2019)
In Identity: A Very Short Introduction, Florian Coulmas refers to an “obsession” (p.1) gripping the world: obsession with identity. In this pocket-size, concise book, he introduces different aspects of identity to demystify this concept in our age. Unlike many books on identity, this volume goes far beyond social and cultural aspects and touches upon the less argued spheres; it examines identity in areas such as philosophy, logics, linguistics, and literature. This book is a successful effort to show why ‘identity’, not just as a term in book titles, but as a concept in human beings’ everyday life, has dominated our world. Identity is as much about sameness as it is about difference. Being constituted of two opposite poles, identity has been and is a mystery to the human mind. After reading this short pocket-size volume, one becomes familiar with different notions of the term ‘identity’ and the traces of its constituents sameness, difference, self, and other in various contexts.